The impact of parental education on earnings: new wine in an old bottle? - John Hudson; John G. Sessions (Institute for the Study of Labor (IZA), 2009)
We examine the impact of parental education on the shape of an individual's experience-earnings profile. A number of factors suggest that parental education will affect the ability of an individual to translate labor market experience into earnings. Our empirical analysis of US data suggests that this is indeed the case. Higher parental education shifts the earnings profile significantly to the left - the profile of individuals with parents who both have 15 years of education peaks at 16 years of experience when their wages are 52% (24%) greater than those whose parents both have only 5 (10) years of education.
urn:nbn:de:101:1-2009060830
Keywords: J30; J31; J33; 330; Parental education; human capital; earnings; Bildungsertrag; Humankapital; Eltern; Familiensoziologie; USA